Initiation of a medical toxicology consult service at a tertiary care children's hospital. (May 2015) - Wang, George Sam; Monte, Andrew; Hatten, Benjamin; Brent, Jeffrey; Buchanan, Jennie; Heard, Kennon J.
Abstract: Currently, only 10% of board-certified medical toxicologists are pediatricians. Yet over half of poison center calls involve children < 6 years, poisoning continues to be a common pediatric diagnosis and bedside toxicology consultation is not common at children's hospitals. In collaboration with executive staff from Department of Pediatrics and Emergency Medicine, regional poison center, and our toxicology fellowship, we established a toxicology consulting service at our tertiary-care children's hospital. There were 139 consultations, and the service generated 13 consultations in the first month; median of 11 consultations per month thereafter (range 8–16). The service increased pediatric cases seen by the fellowship program from 30 to 94. The transition to a consult service required a culture change. Historically, call center advice was the mainstay of consulting practice and the medical staff was not accustomed to the availability of bedside medical toxicology consultations. However, after promotion of the service and full attending and fellowship coverage, consultations increased. In collaboration with toxicologists from different departments, a consultation service can be rapidly established. The service filled a clinical need that was disproportionately utilized for high acuity patients, immediately utilized by the medical staff and provided a robust pediatric population for the toxicology fellowship.